Natural deep eutectic solvents and aqueous solutions as an alternative extraction media for propolis. (November 2019) - Funari, Cristiano Soleo; Sutton, Adam T.; Carneiro, Renato Lajarim; Fraige, Karina; Cavalheiro, Alberto José; da Silva Bolzani, Vanderlan; Hilder, Emily F.; Arrua, R. Dario
Abstract: Ethanolic extracts of propolis are consumed for their health benefits even though direct consumption of alcoholic extracts is not always ideal. Natural Deep Eutectic Solvents (NADES) can potentially extract similar compounds as alcoholic extracts while being better for direct consumption. Therefore, in this work alternative solvents for the extraction of green propolis including its biomarker artepillin C were examined. Sixteen NADES made from low toxicity chemicals, including the essential amino acidl -lysine, were explored along with twelve individual NADES components and honey, which showed similar physical-chemical properties to NADES. At 50 °C NADES made from choline chloride-propylene glycol or lactic acid proved to be equal or better than the benchmark EtOH:Water 7:3 (v/v). Alternatively, aqueousl -lysine appeared as a potential solvent for the preparation of aqueous propolis extracts. From these findings NADES, honey and aqueousl -lysine solutions all demonstrated the potential to replace ethanol or water for extracting green propolis. Graphical abstract: Unlabelled Image Highlights: Green alternatives to ethanol, glycol and water propolis extracts Choline chloride:propylene glycol 1:1 (mol/mol) NADES was the best solvent. 10% w/w aqueousl -lysine extracted 3 times more than pure water. Honey as an extraction solvent Honey shows the same intermolecular structure as NADES.